Psychological Welfare Loss of Land-Expropriated Farmers in China - Xiao, Lifu; Qu, Lu; Wang, Lei; Hu, Zhiling; Xiao, Feilong; Lin, Qiaowen (Frontiers in Environmental Science, 2022)
Mandatory land expropriation, resettlement and welfare loss of landless peasants have received increasing research attention. However, in most previous analyses, the loss of psychological welfare of landless farmers is often neglected, which may lead to biased land requisition compensation and resettlement programs and incomplete policy recommendations. This study attempts to use a three-dimensional framework of place attachment to analyze the causes of psychological welfare loss. China's land expropriation and centralized resettlement cut off the material and emotional ties between farmers and land. Farmers' dependence on land, or their dependence on land-dependent farming lifestyle, has been neglected in the process of land acquisition and resettlement, resulting in the loss of farmers' psychological welfare. Based on a comparative analysis of the existing methods, this paper chooses the contingent valuation method (CVM) to measure the loss of psychological welfare of landless peasants via monetization. The feasibility of the model has been tested at a small scale in nine cities. The results show that 1) farmers have strong place attachment on agricultural land, although centralized land expropriation and resettlement have neglected this dependence and caused psychological welfare losses to landless peasants; and 2) the loss of psychological welfare of landless peasants can be measured by the CVM and presented in monetary units. The monetization measurement method in this paper still has some shortcomings and its feasibility requires more empirical tests. However, as a rare monetization measurement study, this paper can direct academic and policy attention towards this psychological welfare loss.